Dukungan Psikososial Keluarga dalam Pencegahan Pemasungan ODGJ Pasca Pasung di Kabupaten Soppeng - Andi Nur Arifah Apriani Azis; Hidayat Asikin; Rezki Ramdani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Pasung (physical restraint) among people with mental disorders remains a public health problem in Indonesia, particularly in areas with limited access to mental health services and low family knowledge regarding the care of people with mental disorders. Families, as the closest social environment, play an important role in the recovery process and in preventing the recurrence of pasung after release from restraint. This study aimed to analyze the informal roles of families in providing psychosocial support to prevent pasung among people with mental disorders after release from restraint in Soppeng Regency. This study used a qualitative approach with a descriptive design. Informants consisted of family members who had relatives with mental disorders after pasung as general informants and health workers as key informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation and analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results showed that the informal roles of families in preventing pasung include acting as motivators, harmonizers, mediators, caregivers, connectors with health workers, and companions for people with mental disorders. These roles reflect family psychosocial support through meeting basic needs, providing emotional support, supervising medication, and facilitating access to health services. However, limited family knowledge and socio-cultural influences still affect treatment-seeking behavior. Strengthening family roles through mental health education and collaboration with health workers is therefore important to prevent pasung and support social rehabilitation in the community.